Genetic predisposition to thyrotoxicosis and onset of knee osteoarthritis - He, Zhiyi; Gong, Zailing; Jiao, Sizhe; Xiong, Wei; Hao, Xiaoxia; Cui, Jiarui; Zhang, Jiaming (Frontiers in Endocrinology, 2024)
Objective: Thyroid hormones have actions on cartilage, whereas the association between thyroid hormone related diseases and osteoarthritis (OA) are unclear. This study aims to investigate the association between thyrotoxicosis and OA. Methods: Summary-level genetic data of thyrotoxicosis were obtained from FinnGen cohorts (nCase = 10,569, nControl = 762,037). Summary-level data of OA were obtained from a large-scale genome-wide association study of UK Biobank (nCase = 40,659, nControl = 756,338). Single nucleotide polymorphisms (SNPs) robustly associated with thyrotoxicosis or OA were used as genetic instruments. A two-sample bidirectional Mendelian randomization (MR) analysis was designed to assess the effect of genetic predisposition of thyrotoxicosis on OA risk, as well as the reverse their relationship. The causal effect was estimated by Inverse-variance weighted method, with weighted median and MR-Egger as supplementary methods. Results: Genetic predisposition of thyrotoxicosis was associated with the onset of knee OA (autoimmune hyperthyroidism: odds ratio [OR]: 1.05, 95% confidence interval [CI]: 1.03-1.07, FDR < 0.001; thyrotoxicosis: OR: 1.05, 95% CI: 1.02-1.08, FDR = 0.016; thyrotoxicosis with diffuse goitre: OR: 1.04, 95% CI: 1.02-1.07, FDR = 0.003; other and/or unspecified thyrotoxicosis: OR: 1.05, 95% CI: 1.02-1.09, FDR = 0.003), whereas thyrotoxicosis was not associated with hip OA. In reverse MR analysis, genetic predisposition to OA was not associated with thyrotoxicosis. No pleiotropy was identified in the MR analyses. Sensitivity analyses indicated the robustness of the MR estimates. Conclusion: This study provides MR evidence supporting causal association of thyrotoxicosis with knee OA in European population, whereas OA may have no causal effects on thyrotoxicosis.